Prevalence of chronic cough in relation to upper and lower airway symptoms; the Skövde population-based study - Bende, Mats; Millqvist, Eva (Frontiers in Physiology, 2012)
The aim of this study was to determine the prevalence of chronic cough in relation to upper airway symptoms, in a cross-sectional, population-based epidemiological study. Another aim was to relate coughing to other explanatory variables and risk factors. A random sample of 1900 inhabitants from the age of 20, stratified for age and gender, was recruited. Subjects were invited for clinical examinations that included questions about general odor intolerance, respiratory symptoms, and smoking habits, and a smell identification test. In total, 1387 volunteers (73% of the sample) were investigated. The overall prevalence of self-reported chronic cough was 6.3% (95% confidence interval (CI): 5.0-7.6%). Female gender, age, height, BMI, and smoking were significantly related to cough. Furthermore, nasal blockage, nasal secretion, sneezing, asthma, odor and cold air sensitivity, and aspirin intolerance also related to cough with statistical significance, indicating a close connection between chronic cough and upper airway symptoms. In keeping with other studies, this study demonstrates that chronic cough is a widespread problem in society, and is about twice as common in women than in men.